PERANCANGAN DAN PENGUJIAN MESIN CENTRIFUGAL CASTING UNTUK PEMBUATAN KERAMIK TUBULAR - Rahmat Iman Mainil (Sekolah Tinggi Teknologi Pekanbaru, 2014)
entrifugal Casting Machine is a tool that is used to form the ceramic suspension compacted in the mold by utilizing centrifugal force. Design and manufacture of centrifugal casting machines have been successful. Planning theory, analysis and design of appropriate calculation. Mold are mounted on a rotating mold holder with a speed of 20003000 rpm. This machine can be used to produce ceramic products using a small tubular shaped. Ceramic produced in this study using a centrifugal casting machine has 56.8 flexural strength 2 (kg/cm ), the shrinkage of 1.48%, water ab- sorption 20.75%, porosity 29.52% . SEM showed tubular ceramic possessed uniform density and uniform pore size distribution.